PER/BER Performance Evaluation of Less-Complex KVD Decoding Architecture for IEEE 802.11 a/n/ac/ah WLANs - Dutta, R; Konar, SC; Mitra, K (International Journal of Computer Sciences and Engineering, 2025)
In modern era of wireless communications Viterbi decoder (VD) is widely used to decode Binary Convolution Codes (BCC) in many Wi-Fi systems such as WLAN 802.11a/n/ac/ah, Satellite communications, Mobile communications etc. To obtain high decoding performance, the constraint length of BCCs is basically quite long. Whereas the complexity of VD is exponentially affected by BCCs constraint length. Therefore Viterbi decoding of BCCs with long constraint length cannot be used for systems or devices like Internet of Things (IoT) sensors, that require low power and less hardware cost. In this work a less-complex Kmin Viterbi Decoder (KVD) is proposed in which the decoder's complexity is inconsiderably affected by constraint length. For the decoding performance evaluation such as Packet Error Rate (PER) and Bit Error Rate (BER) of the proposed decoder, a BCC with constraint length k = 7 is used. This code is required in Wi-Fi systems such as IEEE 802.11a/n/ac/ah. A new standard 802.11ah for IoT applications is considered for simulation. The PER performance of proposed KVD decoder in relation with several factors such as channel type, modulation type, decoder's trace-back length and packet size has been evaluated. The proposed KVD achieves the same PER performance as the orthodox VD does, while its complexity is reduced by approximately 12.80 times to 21.33 times shown in result analysis.